Laser-induced breakdown spectroscopy and device for simultaneously detecting titanium / zinc content in sunscreen cream

Through fiber laser induced breakdown spectroscopy and improved single-point multi-line calibration method, the digestion problem of titanium dioxide and zinc oxide detection in sunscreen is solved, and efficient and low-cost detection without digestion is achieved.

CN120275376APending Publication Date: 2025-07-08XIAMEN MEDICAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510667403.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

The prior art requires tedious acid digestion treatment when detecting the titanium dioxide and zinc oxide content in sunscreen, and there are problems such as operational risk and high instrument cost. Laser-induced breakdown spectroscopy fails to effectively detect zinc elements in cosmetic analysis.

Method used

Fiber laser-induced breakdown spectroscopy is used to convert sunscreen into solid targets through calcination treatment, and combined with improved single-point multi-line calibration method (OP-MLC), the titanium/zinc content detection is achieved without digestion.

Benefits of technology

It realizes titanium/zinc content detection in sunscreen without digestion, which improves detection accuracy and accuracy, and reduces operating risks and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120275376A_ABST
    Figure CN120275376A_ABST
Patent Text Reader

Abstract

The invention provides a laser-induced breakdown spectroscopy method and device for simultaneously detecting titanium / zinc content in sunscreen cream. The method comprises the following steps: step 1, preparing a sample tablet; 2, preparing a standard product tablet; 3, focusing a laser pulse to the surface of the sample tablet through an optical fiber laser, and collecting a plurality of spectral lines through a micro spectrometer; 4, analyzing the spectrum through a conventional calibration curve method LIBS and an improved single-point multi-line calibration method OP-MLC; according to the technical scheme, the method for detecting the titanium / zinc content in the sunscreen product through the LIBS technology is free of digestion, economical, simple and convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of instrumental analysis, in particular to a laser-induced breakdown spectroscopy method and device for simultaneously detecting titanium / zinc content in sunscreen products. Background Art

[0002] Titanium dioxide (TiO2) and zinc oxide (ZnO) are widely used as inorganic physical sunscreens in sunscreen products due to their effective protection against ultraviolet rays, and their concentrations directly affect the sun protection factor (SPF). However, their use has raised many safety concerns among consumers. Research shows that zinc oxide nanoparticles are toxic to human umbilical vein endothelial cells, epidermal cells, active human keratinocytes and fibroblasts, and may cause cytotoxicity, oxidative stress and DNA damage to the skin. Although the toxicity of titanium dioxide nanoparticles is considered to be lower than that of zinc oxide nanoparticles, they may still pose potential hazards to cell viability, oxidative stress and cell inflammation. Therefore, accurately determining the titanium / zinc content in sunscreen products is crucial for SPF evaluation and daily safety supervision.

[0003] A variety of analytical methods have been applied to detect titanium dioxide (TiO2) and zinc oxide (ZnO) in sunscreen products. Since these materials are mainly used in the form of nanoparticles, a series of studies have systematically evaluated particle size, morphology, number density and crystal structure through techniques such as single particle inductively coupled plasma mass spectrometry (spICP-MS), dynamic light scattering (DLS), transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray diffraction (XRD) and Raman spectroscopy. For the determination of their concentrations in cosmetics, atomic absorption spectroscopy (AAS), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS) are routinely used due to their high maturity, strong stability and excellent detection sensitivity. However, most of these techniques require acid digestion of samples, and TiO2 and ZnO have extremely strong stability in an acidic solution environment, making the digestion process particularly difficult. Therefore, the experimental operation is not only time-consuming and laborious, but also harmful to operators and the environment. Developing acid-free analytical methods has become the focus of attention of researchers.

[0004] X-ray fluorescence spectroscopy (XRF) is a non-destructive elemental detection technique that does not require cumbersome sample pretreatment. Multiple research teams have applied it to the rapid detection of titanium / zinc content in sunscreen products, and its detection limit (LOD) ranges from 0.01% to 0.64%. In addition, scholars such as Zeng have achieved fingerprint imaging research on titanium elements through XRF technology and obtained high-definition fingerprint images. However, this method has a high instrument cost, and special attention needs to be paid to X-ray radiation protection during the experiment. Recently, the Sabbioni team developed a rapid and non-destructive instrumental neutron activation analysis (INAA), which successfully achieved the simultaneous detection of titanium dioxide and zinc oxide in sunscreen products. However, the nuclear reaction instrument system is complex and expensive, which may limit its popularization and application in other laboratories. On the other hand, laser-induced breakdown spectroscopy (LIBS) has been widely applied in multiple fields due to its advantages such as simple instrument structure, low analysis cost, fast detection speed, and simple sample pretreatment. However, due to the soft characteristics of cosmetic matrices, the laser ablation efficiency is low, and the application of this technology in cosmetic analysis is still relatively limited. Scholars such as Menneveux successfully achieved LIBS analysis by concentrating titanium dioxide nanoparticles in the cream matrix on the surface of an aluminum target to form a film, and obtained high-accuracy and precision analysis results by accurately selecting the characteristic spectral lines of titanium elements. The team also used polyvinyl alcohol to solidify the cream matrix to fix the analyte and detected titanium elements by LIBS technology. Good results were obtained for both univariate and multivariate calibrations. However, neither study involved the detection of zinc elements, and the laser irradiance used in the experiment was relatively high (>100 GW / cm 2 ), and it relied on a high-cost Nd:YAG laser.

[0005] In the past decade, fiber laser-induced breakdown spectroscopy (FL-LIBS) has attracted much attention due to its advantages such as economy, high efficiency, stable system, less spectral interference, and moderate sensitivity. However, it has not been developed in the field of cosmetic analysis. Given the high melting point characteristics of titanium dioxide and zinc oxide (about 2000 °C), calcination treatment (up to 800 °C) will not cause significant loss, while the organic matrix will be completely decomposed, converting the originally soft and moist sample into a solid form suitable for LIBS analysis. In addition, the newly proposed one-point multi-line calibration method (OP-MLC) only needs to use a single-concentration standard, and a calibration curve can be constructed through multiple spectral lines to achieve convenient quantification. However, this method does not calculate plasma parameters and is limited in applicability when there are significant matrix effects. Summary of the Invention

[0006] In view of this, the purpose of the present invention is to provide a laser-induced breakdown spectroscopy method and device for simultaneously detecting the titanium / zinc content in sunscreen, and to realize a LIBS technology that is free of digestion, economical and simple for detecting the titanium / zinc content in sunscreen products.

[0007] To achieve the above object, the present invention adopts the following technical solution: A laser-induced breakdown spectroscopy method for simultaneously detecting the titanium / zinc content in sunscreen, comprising the following steps:

[0008] Step 1: Prepare a sample tablet;

[0009] Step 2: Prepare a standard tablet;

[0010] Step 3: Focus the laser pulse onto the surface of the sample tablet through a fiber laser, and collect multiple spectral lines through a micro spectrometer;

[0011] Step 4: Analyze the spectrum by the conventional calibration curve method LIBS and the improved one-point multi-line calibration method (OP-MLC).

[0012] In a preferred embodiment, Step 1 specifically includes: First, weigh about 0.5 g of sunscreen sample and place it in a clean and dry crucible with a known blank firing value. Then, put the crucible into a muffle furnace and calcine it at 800 °C for 2 hours. After the crucible is cooled in a glass desiccator, weigh it again, and calculate the mass of the dry sample powder by deducting the blank firing value of the crucible. Each sample is measured three times repetitively. Carefully transfer the powder to a mortar, manually grind and homogenize it under the irradiation of an infrared lamp to remove moisture, and then pass it through a 300-mesh sieve. Finally, place the powder in a manual powder press and press it under a pressure of 2 tons for 5 minutes to finally obtain a sample tablet with a diameter of 6 mm and a thickness of 1 mm.

[0013] In a preferred embodiment, Step 2 specifically includes: First, prepare TiO2 / ZnO mixed powders with different mass ratios, specifically, the proportions of TiO2 are 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 25%, 50%, 75%, 100%. After homogenization and pressing, they are used as standard tablets for conventional LIBS analysis.

[0014] In a preferred embodiment, in the conventional calibration curve method LIBS, the 3σ criterion is used to calculate the detection limits LOD of titanium (Ti) and zinc (Zn):

[0015] LOD = 3σ / S (1)

[0016] Where σ is the standard deviation of the background signal and S is the slope of the calibration curve.

[0017] In a preferred embodiment, in the improved one-point multi-line calibration method OP-MLC, according to the Boltzmann equation, the emission intensity I at a specific wavelength λ λ is expressed as:

[0018]

[0019] Among them, F is a constant related to the optical efficiency of the collection system, the total particle number density of the plasma, and the volume; C s represents the number concentration of the emitting species; A nm is the transition probability from energy level n to m; g n is the statistical weight of energy level n; E n represents the energy of this energy level; k B is the Boltzmann constant; T refers to the plasma temperature; U s (T) is the partition function of this emitting species; for two emission spectral lines λ1 and λ2 from the same emitting species but different samples, sample a and standard sample b, assuming that the T value is equal under specific experimental conditions, the intensity ratio of the emission spectral lines λ1 and λ2 is expressed as:

[0020]

[0021] Among them, represents the intensity of the emission spectral line λ1, represents the intensity of the emission spectral line λ2, and the subscripts of a and b represent the corresponding parameters in the two samples; represents the number concentration of element s in sample a, represents the number concentration of element s in sample b, is the statistical weight of energy level n of the emission spectral line λ1, is the statistical weight of energy level n of the emission spectral line λ2, is the transition probability from energy level n to m of the emission spectral line λ1, is the transition probability from energy level n to m of the emission spectral line λ2, represents the energy of energy level n of the emission spectral line λ1, represents the energy of energy level n of the emission spectral line λ2, k B is the Boltzmann constant; T refers to the plasma temperature. Assuming that the same emission spectral line λ x is selected for calculation in both sample a and sample b (i.e., λ1 = λ2 = λ x ), then the above equation is rewritten as:

[0022]

[0023] Among them, is the signal intensity of the emission spectral line λ x in sample a, is the signal intensity of the emission spectral line λ x in sample b. By only preparing a standard sample b with a known element concentration C s b and selecting multiple emission spectral lines to calculate Iλx a / I λx b The ratio of, i.e., the unknown concentration C of element s in the unknown sample a is calculated s a . This method is the original single-point multi-line calibration method OP-MLC.

[0024] However, this method assumes that the T values of different samples are equal, and this assumption often does not hold when analyzing complex samples. Therefore, it is necessary to calculate the T values of different samples and include them in the overall calculation process to improve the accuracy of the method. The temperature T was calculated based on the Saha-Boltzmann diagram method:

[0025]

[0026] where λ is the wavelength of a certain emission spectral line, I is the signal intensity of this emission spectral line, m e is the electron mass, E ion is the first ionization energy, and the superscript * indicates that this term needs to be included in the calculation only when λ is an ionic spectral line. N represents the number density of s species, and k, h, and c represent the Boltzmann constant, Planck constant, and speed of light respectively; N e is the electron number density:

[0027]

[0028] where Δλ 1 / 2 , Δλ obs and Δλ ins are the full width at half maximum FWHM of Stark broadening, observed spectral line broadening, and instrument broadening respectively; ω is the Stark broadening parameter of the selected transition; the superscript * in formula (5) indicates that the relevant terms need to be included in the calculation only when applying ionic spectral lines; by linearly fitting the values of each term on the left side of the equation with E n +E ion * , the slope of the obtained straight line is equal to –(1 / kT), and thus the plasma excitation temperature T is calculated; therefore, equation (4) is rewritten as:

[0029]

[0030] where the partition function U s (T) is calculated by formula (8):

[0031]

[0032] Therefore, for a specific emission spectral line I in a specific sample λ ·exp(E n / (k B T))U s(T) items are calculated; by preparing a standard sample b with a known element concentration C s b Select multiple emission spectral lines to calculate the above items for the standard sample b, linearly fit the values of each item in the unknown sample a with the corresponding item values in the standard sample b, and the slope of the obtained regression line can be used to replace the item on the right side of Equation 7, thereby calculating the concentration C of the analyte in the unknown sample s a .

[0033] The present invention also provides a laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen, which operates the above-mentioned laser-induced breakdown spectroscopy method for simultaneously detecting the titanium / zinc content in sunscreen; it includes a fiber laser, a computer, an electronic control card, a micro spectrometer, an optical fiber, an optical fiber probe, a two-dimensional moving platform, a Z-axis moving device, a reflecting mirror, and a focusing lens

[0034] In a preferred embodiment, the two-dimensional moving platform is used to place the sample tablet, and the two-dimensional moving platform is used to drive the sample tablet to move in the horizontal direction; the two-dimensional moving platform is connected to the Z-axis moving device and is used to drive the sample tablet to move in the vertical direction

[0035] In a preferred embodiment, the reflecting mirror, the focusing lens, and the center of the two-dimensional moving platform are located on the same vertical line

[0036] In a preferred embodiment, the optical fiber probe is connected to the micro spectrometer

[0037] In a preferred embodiment, the electronic control card is connected to the computer, the micro spectrometer, and the fiber laser

[0038] Compared with the prior art, the present invention has the following beneficial effects: the present invention converts sunscreen into a solid target by constructing a calcination-assisted sample preparation method, prepares standard samples only by changing the mixing ratio of TiO2 and ZnO, and improves the OP-MLC algorithm for elemental quantitative analysis, aiming to develop a LIBS technology without digestion, economical and simple for detecting the titanium / zinc content in sunscreen products BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the LIBS analysis sample preparation process for the preferred embodiment of the present invention

[0040] Figure 2 It is a schematic diagram of the fiber laser-induced breakdown spectroscopy analysis platform architecture for the preferred embodiment of the present invention

[0041] Figure 3 For the preferred embodiment of the present invention, 0.15 GW / cm 2Schematic diagram of the morphology of laser ablation pits of standard samples of 0%, 25%, 50%, 75%, and 100% TiO2 (TiO2 / ZnO mixture) under laser irradiation;

[0042] Figure 4 For the preferred embodiment of the present invention Figure 3 Spectrograms of the five TiO2 / ZnO mixture standard samples shown;

[0043] Figure 5 Calibration curves of Ti and Zn for the preferred embodiment of the present invention, (a) for Ti and (b) for Zn;

[0044] Figure 6 Schematic diagram of the morphology of laser ablation pits of 11 commercially available sunscreen tablet samples for the preferred embodiment of the present invention;

[0045] Figure 7 Schematic diagram of the plasma temperature and electron density of 11 tablet samples in the LIBS analysis for the preferred embodiment of the present invention;

[0046] Figure 8 Schematic diagram of baseline correction for the preferred embodiment of the present invention, where (a) is the original spectrum and estimated baseline of the 50% TiO2 / ZnO standard sample; (b) is the spectrum after baseline correction.

[0047] Figure 9 Schematic diagram of the Lorentz fitting curves of Ti II 336.1 nm (a) and Zn II 255.7 nm (b) in the 50% TiO2 / ZnO standard sample for the preferred embodiment of the present invention;

[0048] Figure 10 The Y* value of the Saha-Boltzmann curve of Ti and Zn in the 50% TiO2 / ZnO standard sample for the preferred embodiment of the present invention is the left expression of Equation (6). Detailed implementation manners

[0049] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0050] It should be noted that the following detailed description is illustrative and is intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present application belongs.

[0051] It should be noted that the terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the exemplary embodiments according to the present application; as used herein, unless the context clearly indicates otherwise, the singular forms are also intended to include the plural forms. In addition, it should also be understood that when the terms "comprising" and / or "including" are used in this specification, they specify the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0052] A laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen, referring to Figure 2 , includes a fiber laser, a computer, an electronic control card, a micro spectrometer, an optical fiber, an optical fiber probe, a two-dimensional moving platform, a Z-axis moving device, a mirror, and a focusing lens. The two-dimensional moving platform is used to place the sample tablet, and the two-dimensional moving platform is used to drive the sample tablet to move horizontally; the two-dimensional moving platform is connected to the Z-axis moving device and is used to drive the sample tablet to move vertically. The mirror, the focusing lens, and the center of the two-dimensional moving platform are located on the same vertical line. The optical fiber probe is connected to the micro spectrometer. The electronic control card is connected to the computer, the micro spectrometer, and the fiber laser. The computer is connected to the micro spectrometer and the fiber laser.

[0053] A laser-induced breakdown spectroscopy method for simultaneously detecting the titanium / zinc content in sunscreen, applying a laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen; referring to Figure 1 , includes the following steps:

[0054] Step 1: Prepare a sample tablet;

[0055] Step 2: Prepare a standard tablet;

[0056] Step 3: Focus the laser pulse onto the surface of the sample tablet through the fiber laser, and collect multiple spectral lines through the micro spectrometer;

[0057] Step 4: Analyze the spectrum by the conventional calibration curve method LIBS and the improved single-point multi-line calibration method OP-MLC.

[0058] Specifically, as Figure 1As shown, this method removes the organic components in the sunscreen by high-temperature calcination, retains TiO2 and ZnO, and is convenient for detection. The preparation process is as follows: First, weigh about 0.5 g of sunscreen sample and place it in a clean and dry crucible with a known empty-burning value. Then, put the crucible into a muffle furnace and calcine it at 800 °C for 2 hours. After the crucible is cooled in a glass desiccator, weigh it again. The mass of the dried sample powder can be calculated by deducting the empty-burning value of the crucible. Each sample is measured three times repeatedly. Carefully transfer the powder to a mortar, and manually grind and homogenize it under the irradiation of an infrared lamp to remove moisture, and then pass it through a 300-mesh sieve. Finally, place the powder in a manual powder press and press it under a pressure of 2 tons for 5 minutes to finally obtain a tablet sample with a diameter of 6 mm and a thickness of 1 mm.

[0059] Specifically, an economical and efficient low-energy fiber laser is used, and the energy only needs 0.15 GW / cm 2 . This system uses a fiber laser that can emit laser pulses at 1064 nm, and its maximum output power is 50 W. The present invention uses the maximum pulse energy of the laser of 4.17 mJ (which can only be achieved at a pulse width of 350 ns). After measurement, the ablation spot diameter is about 100 μm, and the calculated laser irradiance is as low as 0.15 GW / cm 2 . Figure 2 Shows a schematic diagram of the FL-LIBS instrument device. After the laser pulse is deflected by a mirror, it is focused on the sample surface through a quartz lens with a focal length of 100 mm. The sample is placed on a two-dimensional moving platform, namely an electric XY moving platform. The two-dimensional moving platform is carried on a manual Z-axis platform, and the Z-axis platform is connected to a Z-axis moving device to update the ablation point through the moving platform. Use a vernier caliper to accurately measure the sample thickness, and accordingly adjust the Z-axis height to keep the focusing distance between the lens and the sample surface constant. To maximize the plasma emission light collection efficiency, a fiber optic probe with a core diameter of 600 μm and a numerical aperture of 0.22 is placed unfocused at a horizontal distance of 10 mm and a vertical distance of 5 mm from the ablation point. The collected optical signal is detected by a four-channel Czerny-Turner spectrometer with a slit width of 10 μm, a detection range of 153 - 562 nm, and a spectral resolution of about 0.15 nm. The coordinated control of the fiber laser, the micro spectrometer, and the two-dimensional moving platform is controlled by a self-made electronic control card.

[0060] Specifically, the preparation of the standard product is simple. There is no need to add other reference products. Only TiO2 and ZnO powders need to be weighed and mixed according to a predefined ratio, and the total mass is about 0.1 g. Then, it is calcined, cooled, ground, and tableted under the same experimental parameters as the sunscreen sample. Specific operation method: First, prepare TiO2 / ZnO mixed powders with different mass ratios (TiO2 accounting for 0%, 25%, 50%, 75%, 100%). After homogenization and tablet pressing, they are used as standard samples for conventional LIBS analysis. Figure 3shows 0.15 GW / cm 2 The morphologies of the ablation pits of each standard sample under laser irradiation are shown. It can be seen that as the mass ratio of TiO2 increases, the diameter of the ablation pit gradually increases; however, the thermally induced black ring on the periphery gradually fades, indicating that the range of the heat-affected zone shrinks. This phenomenon shows that the pressed ZnO material has higher thermal conductivity than TiO2, which is beneficial to the conduction of heat from the laser irradiation area to the surrounding, resulting in a smaller ablation pit and a larger heat-affected zone. It can be seen that there is already a significant matrix effect in the FL-LIBS analysis of the binary sample system (TiO2-ZnO). When analyzing actual sunscreen samples, due to the presence of more unknown inorganic salt components, this effect may be further aggravated and affect the analysis performance. Therefore, it is necessary to develop a method for correcting the matrix effect specifically.

[0061] Figure 4 The spectral diagrams of the above five standard samples are shown. It can be seen that the Ti emission lines are highly concentrated within the spectral window, while the Zn emission lines are relatively sparse. In addition, the overall intensity of the Ti spectral lines is significantly higher than that of the Zn spectral lines, which can be partially explained by Figure 3 the higher ablation efficiency of the TiO2 material shown. To construct the calibration curves of the two elements, based on the criteria of high spectral line intensity and small mutual spectral interference, finally, Ti I 368.6 nm and Zn I 330.3 nm are selected as the analytical spectral lines.

[0062] Figure 5 The calibration curves of Ti and Zn are shown. To facilitate comparison between different methods, the oxide mass ratio has been converted to the elemental concentrations of Ti and Zn by the mass fraction of the element in the oxide (Ti accounts for 80.34% in TiO2, and Zn accounts for 59.93% in ZnO). It can be seen that the Zn calibration curve shows good linearity within the entire research concentration range ( Figure 5 b), while the Ti intensity shows non-linear variation, and obvious different trends are presented in the low and high concentration ranges. For clear distinction, TiO2 / ZnO standard samples with Ti concentrations of 12, 24, 36, 48, 60, 72, 84, 96, and 108 mg / g are further prepared and analyzed, and the results are as shown in Figure 5 a. The curve shows two significant change stages: the intensity rising rate in the low concentration region (slope = 248.37) is much higher than that in the high concentration region (slope = 32.27), and the turning point is approximately located at (78 mg / g, 19500). Therefore, for the calculation of the Ti concentration of unknown samples, it is necessary to select the corresponding calibration curve according to whether the spectral line intensity exceeds 19500.

[0063] Specifically, analysis was carried out by the conventional calibration curve LIBS method and the self-developed improved one-point multi-line calibration (OP-MLC) method. By the conventional LIBS method, the limits of detection (LOD) for Ti and Zn were 0.046 mg / g and 0.473 mg / g, respectively, which were sufficient to detect these low-concentration elements in commercially available sunscreen products. However, its relative quantitative error was relatively high, and it was found to be related to the matrix effect, which was significantly correlated with the concentration of TiO2. To correct this error, the OP-MLC method was self-developed and improved by incorporating plasma parameters into the calculation, and its accuracy was twice that of the conventional LIBS method and three times that of the original OP-MLC method. At the same time, since multiple spectral lines were used to offset the signal fluctuations in repeated measurements, the analysis accuracy was also improved compared with the conventional laser-induced breakdown spectroscopy method. However, when detecting low-concentration analytes, this method may not be applicable because low-intensity spectral lines may disappear. Therefore, by combining these two methods, the titanium / zinc content in sunscreen can be accurately determined, as shown in Table 1 and Table 2.

[0064] Table 1 Detection results of Ti / Zn in 11 commercially available sunscreen products by different methods

[0065]

[0066] Table 2 Relative quantitative errors of different detection methods

[0067]

[0068]

[0069] The specific method of the conventional LIBS method is as follows: The limits of detection (LOD) of titanium (Ti) and zinc (Zn) were calculated using the classical 3σ criterion:

[0070] LOD = 3σ / S (1)

[0071] where σ is the standard deviation of the background signal (estimated by the standard deviation of the background signal at wavelengths adjacent to the analysis line), and S is the slope of the calibration curve. The calculated LODs of Ti and Zn in the dry-based sample were 0.22 mg / g and 2.23 mg / g, respectively. However, since the actual sunscreen products are viscous, analysts and consumers are more concerned about the weight concentration. Therefore, the present invention further determined the ash content ratio after calcination (Table 3). The average ash content ratio of 11 sunscreen products was 21.21%, and this value was used for the conversion between the dry-based concentration and the weight concentration in subsequent analyses. Finally, the actual wet-based LODs of Ti and Zn were calculated to be 0.046 mg / g and 0.473 mg / g, respectively. This method was sufficient to detect these low-concentration elements in commercially available sunscreen products.

[0072] Table 3 Study on the ash content ratio of 11 samples

[0073]

[0074] The main reason for the decrease in quantitative accuracy between conventional LIBS and the original OP-MLC method may be related to the significant matrix effect. Figure 6 The laser ablation pit morphology of 11 pressed samples is shown. Combined with the ablation pit characteristics of TiO2 / ZnO standard sample ( Figure 3 ) analysis shows that: with the change of TiO2 / ZnO ratio in the tablet, the morphology and color of the ablation pit change significantly; and other functional inorganic salts / mineral components that may be added in the actual sunscreen will further aggravate this difference. This leads to differences in the mass of ablated materials and the number of ionized electrons in different samples, which in turn affects the laser-plasma interaction process, causing the plasma temperature (T) and electron density (N e )fluctuation( Figure 7 ). The maximum difference of T is 103K, N e The maximum difference is 2.3×10 16 cm -3 , which is high enough to cause nonlinear deviations in conventional LIBS and original OP-MLC analysis. Further observation revealed that high T / N e The ablation pits of samples (No. 1, 5, 9, 11) are dark ( Figure 6 ), and the characteristics of the high TiO2 content standard sample ( Figure 3 ) and the corresponding high Ti concentration test results (Table 1). This shows that a high TiO2 ratio is more conducive to laser ablation and plasma excitation processes, which may be the main source of matrix effect. The modified OP-MLC method proposed in this invention introduces T and N in the calculation e The parameters were adjusted to effectively correct the matrix effect, and experiments showed that its quantitative accuracy was significantly improved.

[0075] Specifically, the innovative improved single-point multi-line calibration (OP-MLC) method can be used to achieve convenient quantification by using a single concentration standard and constructing a calibration curve through multiple spectral lines, and the relative quantitative error is small, as shown in Table 2. Under the assumption that the plasma is in an optically thin state and local thermal equilibrium (LTE), according to the Boltzmann equation, the emission intensity I at a specific wavelength λ λ It can be expressed as:

[0076]

[0077] where F is a constant related to the optical efficiency of the collection system, the total plasma particle density and volume; C s represents the number concentration of the emitting species; A nm is the transition probability from energy level n to m; g n is the statistical weight of energy level n; En represents the energy of this energy level; k B is the Boltzmann constant; T refers to the plasma temperature; U s (T) is the partition function of this emitting species. For two emission spectral lines λ1 and λ2 from the same emitting species but different samples (sample a and sample b), assuming that the T value is equal under specific experimental conditions, their intensity ratio can be expressed as:

[0078]

[0079] where the subscripts of a and b represent the corresponding parameters in the two samples. If λ1 = λ2 = λ x , then the above equation can be rewritten as:

[0080]

[0081] By only preparing a standard sample b (C s b ) with a known element concentration, and selecting multiple emission spectral lines to calculate the ratio of I λx a / I λx b , the unknown concentration C s a can be calculated. This method is the original single-point multi-line calibration method OP-MLC. However, this method assumes that the matrix effect must be extremely low on the premise that the temperature T is the same in different samples, which needs to be carefully evaluated and often does not hold in complex sample systems. Therefore, in order to fully consider the influence of the matrix effect in the present invention, the temperature T is calculated according to the Saha-Boltzmann diagram method:

[0082]

[0083] where m e is the electron mass, E ion the first ionization energy (6.82 eV for Ti and 9.39 eV for Zn), N represents the number density of the s species, and k, h, and c represent the Boltzmann constant, Planck constant, and speed of light respectively. N e is the electron number density, which can be determined by the Stark broadening method:

[0084]

[0085] where △λ 1 / 2 , △λ obs and △λ insare the full width at half maximum (FWHM) of Stark broadening, observed spectral line broadening, and instrumental broadening, respectively; ω is the Stark broadening parameter for the selected transition. The superscript * in Equation (5) indicates that the relevant terms need to be included in the calculation only when applying ionic spectral lines. By linearly fitting the values of each term on the left side of the equation to E n +E ion * , the slope of the resulting straight line is equal to –(1 / kT), from which the plasma excitation temperature T can be calculated. Therefore, Equation (4) can be rewritten as:

[0086]

[0087] where the partition function U s (T) is calculated by Equation (8):

[0088]

[0089] Therefore, for a specific emission spectral line in a specific sample, the term I λ ·exp(E n / (k B T))U s (T) can be calculated. By preparing a standard sample b with a known analyte concentration C s b , selecting multiple emission spectral lines to calculate the above terms respectively, linearly fitting the values of each term in the unknown sample a to the corresponding term values in the standard sample b, the slope of the resulting regression straight line can be used to replace the term on the right side of Equation 7, thereby calculating the analyte concentration C s a in the unknown sample.

[0090] To accurately calculate plasma parameters, the influence of background emission needs to be eliminated. The present invention uses the moving minimum method to estimate and subtract the spectral baseline. This method is widely used because of its simple operation, fast speed, and strong stability. Figure 8 a shows the original spectrum of a standard sample containing 50% TiO2 and ZnO with a laser energy of 4.16 mJ. Although the delayed acquisition technique reduces the intensity of continuous background emission, there are still obvious fluctuations in the baseline. After baseline subtraction, the spectral baseline returns to zero, and the shape of each spectral line remains unchanged ( Figure 8 (b)). This result indicates that the baseline subtraction process is effective and helps to obtain the accurate net intensity of emission spectral lines. Several common atomic spectral lines and ionic spectral lines of Ti and Zn are marked in the figure.

[0091] After baseline correction, based on the above Stark broadening mechanism, the electron density (N e)。To reduce the self-absorption effect, two ionic spectral lines, Ti II 336.1 nm (ω = 7.02 pm) and Zn II 255.7 nm (ω = 44 pm), were selected for calculation, and the Lorentz fitting results were shown using the spectrum of a 50% TiO2 / ZnO standard sample ( Figure 9 ). The calculated N values of Ti and Zn e were (3.27 ± 0.35) × 10 6 cm -3 and (4.54 ± 0.36) × 10 6 cm -3 respectively, and the two were in good agreement. The average of the two was taken in the subsequent temperature (T) calculation.

[0092] After determining N e , based on the above theoretical framework, the Saha-Boltzmann curve method was used to calculate the plasma temperature (T). Identifiable Ti and Zn non-resonant atomic spectral lines and ionic spectral lines were selected (Table 4). As Figure 10 shown, the linear regression fitting effects of Ti and Zn were good. Taking the 50% TiO2 / ZnO standard sample as an example, the calculated T values of Ti and Zn were (4480 ± 96) K and (5450 ± 107) K respectively, and the two had good consistency. The average of the two was taken in the subsequent corrected OP-MLC calculation.

[0093] Table 4 Titanium (Ti) and zinc (Zn) transition data used in the present invention

[0094]

[0095] It should be noted that compared with the common plasma parameters in the LIBS analysis of metal samples (usually reaching above 10000 K and on the order of 10 2 under laser irradiation in the GW / cm 17 cm -3 order of magnitude), the T and N e values of the present invention are relatively low. This may be due to the lack of metallic bond electrons in the crystal characteristics of TiO2 and ZnO, resulting in a lower coupling efficiency between laser photons and electrons, and a reduced proportion of laser energy converted into the sample heating and plasma generation process. Existing technologies show that under the irradiation of a 1064 nm laser at 10 GW / cm 2 , the plasma temperature generated by pressing a ZnO powder sheet is about 6000 K and the electron density is about 1.4 × 10 16 cm -3 , which is of the same order of magnitude as the corresponding parameters of the present invention.

[0096] The present invention uses the McWhirter criterion as a necessary condition for evaluating the local thermodynamic equilibrium LTE state of the plasma, and its expression is:

[0097] N e >1.6×10 12 T 1 / 2 △E 3 (9)

[0098] where ΔE represents the electron transition energy of the emission line. Taking the 50% TiO2 / ZnO standard sample as an example, the highest electron density required for LTE calculated according to the emission lines used in this experiment is 1.37×10 16 cm -3 , and the above calculation results show that this condition can be satisfied. However, just satisfying the McWhirter criterion is not sufficient to fully characterize the LTE state of the plasma. Therefore, we further evaluate the optically thin state of the plasma through the self-absorption coefficient (SA):

[0099]

[0100] where α is usually taken as -0.54. The SA value ranges from 0 to 1, and the larger the value, the weaker the self-absorption effect. Substituting the relevant data of Ti II 336.1 nm and Zn II 255.7 nm for calculation, the average SA value is 0.28. This value is relatively high compared with the typical data of the Nd:YAG laser LIBS, confirming that the plasma in the present invention is in a good optically thin state.

Claims

1. A laser-induced breakdown spectroscopy method for simultaneously detecting titanium / zinc content in sunscreen, characterized in that, Including the following steps: Step 1: Prepare a sample tablet; Step 2: Prepare a standard tablet; Step 3: Focus laser pulses onto the surface of the sample tablet through a fiber laser, and collect multiple spectral lines through a micro spectrometer; Step 4: Analyze the spectrum by the conventional calibration curve method LIBS and the improved single-point multi-line calibration method OP-MLC.

2. The laser-induced breakdown spectroscopy method for simultaneously detecting titanium / zinc content in sunscreen according to claim 1, characterized in that, Step 1 specifically includes: First, weigh about 0.5 g of sunscreen sample and place it in a clean and dry crucible with a known blank firing value. Then, put the crucible into a muffle furnace and calcine it at 800 °C for 2 hours. After the crucible cools in a glass desiccator, weigh it again, and calculate the mass of the dry sample powder by deducting the blank firing value of the crucible. Each sample is determined three times repetitively. Carefully transfer the powder to a mortar, and manually grind and homogenize it under the irradiation of an infrared lamp to remove moisture, and then pass it through a 300-mesh sieve. Finally, place the powder in a manual powder press and press it under a pressure of 2 tons for 5 minutes to finally obtain a sample tablet with a diameter of 6 mm and a thickness of 1 mm.

3. A laser-induced breakdown spectroscopy method for simultaneously detecting titanium / zinc content in sunscreen according to claim 1, characterized in that, Step 2 specifically includes: First, prepare TiO2 / ZnO mixed powders with different mass ratios, specifically, the proportion of TiO2 is 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 25%, 50%, 75%, 100%; after homogenization and pressing, it is used as a standard tablet for conventional LIBS analysis.

4. A laser-induced breakdown spectroscopy method for simultaneously detecting the titanium / zinc content in sunscreen according to claim 1, characterized in that, In the conventional calibration curve method LIBS, the 3σ criterion is used to calculate the detection limits LOD of titanium Ti and zinc Zn: LOD = 3σ / S (1) In the formula, σ is the standard deviation of the background signal, and S is the slope of the calibration curve.

5. A laser-induced breakdown spectroscopy method for simultaneously detecting titanium / zinc content in sunscreen according to claim 1, characterized in that In the improved one-point multi-line calibration method OP-MLC, according to the Boltzmann equation, the emission intensity I at a specific wavelength λ λ is expressed as: where F is a constant related to the optical efficiency of the collection system, the total plasma particle number density, and the volume; C s represents the number concentration of the emitted particles s; A nm is the transition probability from energy level n to m; g n is the statistical weight of energy level n; E n represents the energy of this energy level; k B is the Boltzmann constant; T refers to the plasma temperature; U s (T) is the partition function of this emitting species; for two emission spectral lines λ1 and λ2 of the same emitting species but different samples, sample a and standard sample b, assuming that the T values of a and b are equal under specific experimental conditions, the intensity ratio of the emission spectral lines λ1 and λ2 is expressed as: Among them, represents the intensity of the emission spectral line λ1, represents the intensity of the emission spectral line λ2, and the superscripts of a and b represent the corresponding parameters in the a sample and the b sample; represents the number concentration of element s in the a sample, represents the number concentration of element s in the b sample, is the statistical weight of the energy level n of the emission spectral line λ1, is the statistical weight of the energy level n of the emission spectral line λ2, is the transition probability from the energy level n to m of the emission spectral line λ1, is the transition probability from the energy level n to m of the emission spectral line λ2, represents the energy of the energy level n of the emission spectral line λ1, represents the energy of the energy level n of the emission spectral line λ2, k B is the Boltzmann constant; T refers to the plasma temperature. It is assumed that the same emission spectral line λ x is selected for calculation in both the a sample and the b sample, that is, λ1 = λ2 = λ x , then the above equation is rewritten as: Among them, is the signal intensity of the emission spectral line λ x in sample a, is the signal intensity of the emission spectral line λ x in sample b. Only by preparing a standard sample b with a known element concentration C s b and selecting multiple emission spectral lines to calculate the ratio of I λx a / I λx b , the unknown concentration C s a of element s in the unknown sample a can be calculated; The temperature T is calculated based on the Saha-Boltzmann diagram method: where λ is the wavelength of a certain emission spectral line, I is the signal intensity of this emission spectral line, m e is the electron mass, E ion is the first ionization energy, and the superscript * indicates that this term needs to be included in the calculation only when λ is an ionic spectral line. N represents the number density of species s, and k, h, and c represent the Boltzmann constant, Planck's constant, and the speed of light respectively; N e is the electron number density: where, △λ 1 / 2 , △λ obs and △λ ins are the full width at half maximum (FWHM) of Stark broadening, observed spectral line broadening, and instrument broadening, respectively; ω is the Stark broadening parameter of the selected transition; by linearly fitting the values of each term on the left side of the equation to E n +E ion * , the slope of the resulting straight line is equal to –(1 / kT), from which the plasma excitation temperature T is calculated; therefore, Equation (4) is rewritten as: Among them, the partition function U s (T) is calculated by Equation (8): Therefore, calculate the I λ ·exp(E n / (k B T))U s (T) term for a specific emission spectral line in a specific sample; by preparing a standard sample b with a known element concentration C s b , select multiple emission spectral lines to calculate the above terms respectively, linearly fit the values of each term in the unknown sample a with the corresponding term values in the standard sample b, and the slope of the obtained regression line can be used to replace the term on the right side of Equation 7, so as to calculate the concentration C s a of the analyte in the unknown sample.

6. A laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen, characterized in that Run a laser-induced breakdown spectroscopy method for simultaneously detecting the titanium / zinc content in sunscreen as described in any one of claims 1-5 above; Including a fiber laser, a computer, an electronic control card, a micro spectrometer, an optical fiber, an optical fiber probe, a two-dimensional moving platform, a Z-axis moving device, a mirror, and a focusing lens.

7. A laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen according to claim 6, characterized in that, The two-dimensional moving platform is used to place the sample tablet, and the two-dimensional moving platform is used to drive the sample tablet to move horizontally; the two-dimensional moving platform is connected to the Z-axis moving device and is used to drive the sample tablet to move vertically.

8. A laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen, characterized in that, The centers of the mirror, the focusing lens, and the two-dimensional moving platform are located on the same vertical line.

9. The laser-induced breakdown spectroscopy device for simultaneously detecting titanium / zinc content in sunscreen according to claim 6, wherein The optical fiber probe is connected to the micro spectrometer.

10. A laser-induced breakdown spectroscopy device for simultaneously detecting the titanium / zinc content in sunscreen, characterized in that, The electronic control card is connected to the computer, the micro spectrometer, and the fiber laser.